2015
DOI: 10.1371/journal.pone.0128964
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Reactivity Is Increased 4-6 Weeks Postpartum in Healthy Women: A Longitudinal fMRI Study

Abstract: Marked endocrine alterations occur after delivery. Most women cope well with these changes, but the postpartum period is associated with an increased risk of depressive episodes. Previous studies of emotion processing have focused on maternal–infant bonding or postpartum depression (PPD), and longitudinal studies of the neural correlates of emotion processing throughout the postpartum period in healthy women are lacking. In this study, 13 women, without signs of post partum depression, underwent fMRI with an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 63 publications
2
58
0
Order By: Relevance
“…Although this may appear contradictory to prior reports, it is suggested that, in this non‐clinical sample of mothers in the early postpartum period, subclinical levels of depression may capture an emotional experience that is qualitatively distinct from PPD and may in fact reflect normal or even healthy response to adjusting to the stress of new motherhood. Similar results were documented by Gingnell et al with regard to the insula, a region involved in integrating affective cues and producing emotions . In their sample of non‐depressed mothers 4‐6 weeks postpartum compared to non‐pregnant control women, increased reactivity of the insula to negative emotional adult faces (vs sensorimotor control) was positively correlated with the mothers’ subclinical depressive symptoms.…”
Section: The Maternal Brain In Postpartum Depressionsupporting
confidence: 85%
See 3 more Smart Citations
“…Although this may appear contradictory to prior reports, it is suggested that, in this non‐clinical sample of mothers in the early postpartum period, subclinical levels of depression may capture an emotional experience that is qualitatively distinct from PPD and may in fact reflect normal or even healthy response to adjusting to the stress of new motherhood. Similar results were documented by Gingnell et al with regard to the insula, a region involved in integrating affective cues and producing emotions . In their sample of non‐depressed mothers 4‐6 weeks postpartum compared to non‐pregnant control women, increased reactivity of the insula to negative emotional adult faces (vs sensorimotor control) was positively correlated with the mothers’ subclinical depressive symptoms.…”
Section: The Maternal Brain In Postpartum Depressionsupporting
confidence: 85%
“…Furthermore, insular reactivity significantly increased from 48 hours postpartum to 4‐6 weeks postpartum. Although, the increased insular reactivity observed in this non‐clinical sample of mothers is similarly interpreted as reflecting normal postpartum adaptation, Gingnell et al also raise the possibility that these normal adaptive changes in the postpartum period may place women at an increased risk of PPD, as reflected in the positive correlations observed between these changes and depressive symptoms. We tentatively draw from the conclusions of both Swain and Gingnell et al that normative early postpartum adaptation may involve an increase in, at least part of, salience network reactivity.…”
Section: The Maternal Brain In Postpartum Depressionmentioning
confidence: 75%
See 2 more Smart Citations
“…within 48 hours and 4–6 weeks) in 13 healthy postpartum women and 15 naturally cycling non-pregnant controls (54). Early postpartum women had lower reactivity in right insula, left middle frontal gyrus, and bilateral inferior frontal gyrus when compared to late postpartum women.…”
Section: Methodsmentioning
confidence: 99%